Kecakapan Berpikir Dalam Konteks Pendekatan Pembelajaran Pada Kurikulum Sekolah Di Indonesia - Marwan Salahuddin; Fatimatul Asroriyah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2019)
The thinking skills are indispensable in the context of the learning approach, as it is a scientific thinking process aimed at growing the expected personality. It also affects the learning process and the ability to develop its goals through strengthening attitudes, skills and knowledge in an integrated way. The process includes activities: observing, asking, trying, reasoning, and communicating. In the course of the school curriculum in Indonesia and its learning process, the strengthening of cognitive and skill aspects is still dominant, while the attitude (spiritual and social) is still lacking, but this attitude will support the learning activities oriented to cultivation of character. Because the curriculum and the previous learning process still appear to be opposite and have not indicated the process of achieving competence in the attitude aspect, the curriculum of the school applied today is tailored to that need. So as to accommodate the elements of personality that include: beliefs, values, and behavior as a whole.